ANALISIS DISIPLIN KERJA PETUGAS SUKU DINAS PENANGGULANGAN KEBAKARAN DAN PENYELAMATAN JAKARTA - Adinda Tri Wahyuni; Christian Wiradendi Wolor; Eka Dewi Utari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyse the work discipline of officers at the Central Jakarta Fire and Rescue Service. The focus of the study includes compliance with standard operating procedures (SOPs), factors that influence work discipline, and its impact on the effectiveness and speed of response in emergency situations. The research used a descriptive qualitative approach with data collection techniques in the form of interviews, observation, and documentation. The results show that officer discipline is generally high, but there are still technical obstacles and inconsistencies that affect team performance. Factors such as leadership, sanction and reward system, and supervision play a significant role in shaping disciplinary behaviour. This research confirms the importance of sustainable disciplinary management to support smooth operations and public safety.